MALAYSIA A MARITIME NATION AGENDA STEERING THE COURSE - Andrew, Ivan Mario; Nazli Aziz (Royal Malaysian Navy Sea Power Centre (RMN SPC), 2023)
Malaysia is blessed with all the attributes of a maritime nation with continental roots. Our strategic location, between the Indian Ocean and the Asia Pacific region, makes us the focus of global maritime trade, whereby 90 per cent is via shipping. In addition to maritime trade, our beautiful coastlines and islands are major attractions that boost tourism, while the bountiful resources in our waters, both living and non-living, provide important benefits to many economic sectors, ranging from aquaculture to the oil and gas industries. The maritime sector's contributions towards the growth and dynamism of our economy will become more significant as we aspire to become a fully developed nation.